Integrated information and communication technologies for farm-level access to natural resource management information - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Project that addresses the disparity in farmers’ information needs and their access to information. It integrates information and communication technologies that connected farmers to appropriate information using multiple information sources and media including telecentres and village information centres. The centres were equipped with portable phones, printed materials like leaflets, brochures, pamphlets, research reports and books.